Religion und Städtekonkurrenz Zum politischen und kulturellen Kontext von Pausanias' Periegese - Frateantonio, Christa (Millennium-Studien / Millennium Studies, 2009)
Christa Frateantonio follows a new line of research in this study of Pausanias` Periegesis, his historical and geographical description of Greece.Her underlying premise is that it is in fact concealed praise (or criticism) of cities, and supports this view by drawing attention to intention "riddles" in the Periegesis. These she expounds in detailed textual analyses, and explains the structures of the work, some of which are unexplained, as the result of rhetorical principles of description, which she considers in their relationship to the cultural context of the Second Sophistic.